Exact Solution of Four-Coupled Nonidentical Kuramoto Oscillators at a Full Phase Locked State - Mahmoud, M. S. (2023)
We consider a Kuramoto model of four-coupled oscillators of nonidentical initial frequencies. Under the influence of coupling, the oscillators fall into a full phase locked state of a common frequency when the coupling strength surpasses a threshold value. We find numerically the parameters that control this distinguishable coupling constant at the moment the oscillators transit into an entire frequency synchronization when a complete phase lock state takes place. We are able to set apart a recognizable phase condition at the fully locked state. This phase condition helps to derive an analytic formula to calculate the coupling factor as soon as the oscillators depart to a full phase locking state. The explicit expression of the edge coupling factor is given in terms of the initial frequencies of the four oscillators. The formula valid for calculating the distinct coupling allows to find mathematical expressions to calculate the phase differences when the four-coupled phase oscillators are strictly at the full phase locked state and have a common frequency synchronization.